2020
DOI: 10.1016/j.carbon.2019.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Structural, electronic and mechanical properties of all-sp2 carbon allotropes with density lower than graphene

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…[3][4][5] Recent studies indicate that introducing defects into pristine graphene is a good strategy to suppress the formation of lithium clusters on the surface of graphene. 4,6,7 Although the presence of structural defects such as vacancy and Stone-Wales defects destroys the perfect symmetry of graphene; it also produces many local electron-deficient regions around the defects [8][9][10] and many effective adsorption positions for lithium atoms on the surface of graphene. This results in a significant increase in the lithium storage capacity of graphene nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recent studies indicate that introducing defects into pristine graphene is a good strategy to suppress the formation of lithium clusters on the surface of graphene. 4,6,7 Although the presence of structural defects such as vacancy and Stone-Wales defects destroys the perfect symmetry of graphene; it also produces many local electron-deficient regions around the defects [8][9][10] and many effective adsorption positions for lithium atoms on the surface of graphene. This results in a significant increase in the lithium storage capacity of graphene nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In KG, using a larger simulation size can begin to illustrate otherwise unobserved behavior under loading, such as wrinkling, which would not be observed on sub-nanometer length scales. There has been limited work on KG's mechanical properties using small (less than 1000 atom) DFT simulations [15,16]. Similarly, Zhao et al [8] reported use of a molecular static study to test the material properties of three graphene allotropes, including "cyclicgraphene" as named, which has a similar atomic structure of KG of this study.…”
Section: Introductionmentioning
confidence: 75%
“…In Ref. [86], where two metallic materials were predicted-tilene and flakene -two more materials were described as semiconductors -liskene and liskenedaughter.…”
Section: Pseudo-graphene Crystals With Semiconductor Electronic Band Structurementioning
confidence: 99%
“…This material is predicted to remain stable below 1000 K. Later in 2019, in Ref. [86] -tilene and flakene were described as metals thermal stability up to 500 K. Tilene's Young's module and Poisson's ratio are 0.235 TPa and 0.607, respectively, and UTS is 44.8 GPa. Flakene's Young's module and Poisson's ratio are 0.115 TPa and 0.746, respectively, and UTS is 23.6 GPa.…”
mentioning
confidence: 99%
See 1 more Smart Citation